Adaptive importance sampling for performance evaluation and parameter optimization of communication systems. - Remondo, D.
We present new adaptive importance sampling techniques based on stochastic Newton recursions. Their applicability to the performance evaluation of communication systems is studied. Besides bit-error rate (BER) estimation, the techniques are used for system parameter optimization. Two system models that are analytically tractable are employed to demonstrate the validity of the techniques. As an application to situations that are analytically intractable and numerically intensive, the influence of crosstalk in a wavelength-division multiplexing (WDM) crossconnect is assessed. In order to consider a realistic system model, optimal setting of thresholds in the detector is carried out while estimating error rate performances. Resulting BER estimates indicate that the tolerable crosstalk levels are significantly higher than predicted in the literature. This finding has a strong impact on the design of WDM networks. Power penalties induced by the addition of channels can also be accurately predicted in short run-times
Keywords: AWGN; BER estimates; BER estimation; DPSK receiver; OOK receiver; WDM crossconnect; WDM network design; Adaptive importance sampling; Additive white Gaussian noise; Analytically intractable systems; Analytically tractable system models; Bit-error rate; Communication systems; Crosstalk; Detector thresholds; Differential phase-shift keying; Error rate performance; Noncoherent on-off keying; Parameter optimization; Performance evaluation; Power penalties; Short run-times.; Stochastic Newton recursions; Wavelength-division multiplexing